Remote optogenetic control of the enteric nervous system and brain-gut axis in freely-behaving mice enabled by a wireless, battery-free optoelectronic device - Efimov, Andrew I.; Hibberd, Timothy J.; Wang, Yue; Wu, Mingzheng; Zhang, Kaiqing; Ting, Kaila; Madhvapathy, Surabhi; Lee, Min-Kyu; Kim, Joohee; Kang, Jiheon; Riahi, Mohammad; Zhang, Haohui; et al. (Pergamon Press Ltd., 2024)
Wireless activation of the enteric nervous system (ENS) in freely moving animals with implantable optogenetic devices offers a unique and exciting opportunity to selectively control gastrointestinal (GI) transit in vivo, including the gut-brain axis. Programmed delivery of light to targeted locations in the GI-tract, however, poses many challenges not encountered within the central nervous system (CNS). We report here the development of a fully implantable, battery-free wireless device specifically designed for optogenetic control of the GI-tract, capable of generating sufficient light over large areas to robustly activate the ENS, potently inducing colonic motility ex vivo and increased propulsion in vivo. Use in in vivo studies reveals unique stimulation patterns that increase expulsion of colonic content, likely mediated in part by activation of an extrinsic brain-gut motor pathway, via pelvic nerves. This technology overcomes major limitations of conventional wireless optogenetic hardware designed for the CNS, providing targeted control of specific neurochemical classes of neurons in the ENS and brain-gut axis, for direct modulation of GI-transit and associated behaviours in freely moving animals.